2013
DOI: 10.1016/j.repc.2013.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Selection of patients for percutaneous balloon mitral valvotomy: Is there a definitive limit for the Wilkins score?

Abstract: PBMV was a safe and effective procedure in patients in the WS gray zone. Optimal results can be achieved in these patients if they are carefully selected and operated at experienced centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Paiva et al [19] noticed none significant differences between patients with score 9 -11 and patients with score < 8 regarding major complication or success rate. Pre-operative transthoracic echocardiography also showed that patients who developed severe MR had higher incidence of other valvular lesions, MV commissural calcification, pre-operative MR, and higher prevalence of AF.…”
Section: Discussionmentioning
confidence: 92%
“…Paiva et al [19] noticed none significant differences between patients with score 9 -11 and patients with score < 8 regarding major complication or success rate. Pre-operative transthoracic echocardiography also showed that patients who developed severe MR had higher incidence of other valvular lesions, MV commissural calcification, pre-operative MR, and higher prevalence of AF.…”
Section: Discussionmentioning
confidence: 92%